Narratives of Brazilian Modernism. Tarsila do Amaral and the Anthropophagic Movement as Aesthetic Decolonization - Lucero, María Elena (Universidad Pedagógica y Tecnológica de Colombia, 2015)
Tarsila do Amaral (1886-1973) began her anthropophagic phase in 1928, after the creation of Abaporú, a painting that insinuated the consequent writing of the Anthropophagic (or Cannibalist) Manifesto by Oswald de Andrade in the same year. These proposals formulated ´anthropophagy´ as a devouring of the colonizer, assimilating certain aspects, discarding others and promoting a version of the native that eats the other without shame. In this way, the political proile of anthropophagy in Brazil created visual or literary rhetorical strategies to undo colonialist mechanisms of domination.This article attempts to read the trajectory of Tarsila, taking the painting Anthropophagy, from 1929, as epicenter, a work that operated as a decolonizing challenge to the dominant eurocentric aesthetics based on Western iconography. Inthis image the igures blend into their own environment, imbued in a visual gigantism that can seem threatening. The surrounding jungle recreated a version of tropicalism as a space of power or synergy set in a local atmosphere, which distanced itself from preconcieved ways of symbolizing the Brazilian landscape, and reconstructed a vigorous visuality that confronted the stereotyped invention of the American landscape.